Antimicrobial volatiles emitted by members of the nest microbiome of social spiders. Issue 1 (7th September 2022) - Lammers, Alexander; Nazipi, Seven; Zweers, Hans; Bilde, Trine; Schramm, Andreas; Garbeva, Paolina; Lalk, Michael
Abstract: Microbes produce and respond to a range of structurally and functionally diverse volatiles. Many microbial volatiles have antimicrobial properties. Since volatiles can diffuse through complex 3D systems like spider nests, they are promising pathogen protection for social arthropods. Here, we analyzed the volatilomes of five nest microbiome members of the Namibian, social spider Stegodyphus dumicola, namely the bacteria Massilia sp. IC2-278, Massilia sp. IC2-477, Sphingomonas sp. IC-11, Streptomyces sp. IC-207, and the fungus Aureobasidium sp. CE_32, and tested their antimicrobial activity against two putative spider pathogens, namely Bacillus thuringiensis and Purpureocillium lilacinum . Most nest microbiome members released volatilomes with antibacterial and/or antifungal activities under in vitro conditions. The analysis of their volatilomes using GC/Q-TOF revealed that they include numerous antimicrobial volatiles. We tested the antimicrobial activity of five pure volatile compounds found in the volatilomes and revealed that all of them were antibacterial and/or antifungal. We could not identify the same antimicrobial volatiles as in a previous in situ study, but our results indicate that social spider-associated microorganisms as a source of antimicrobial volatiles are important for pathogen inhibition. Additionally, we showed the influence of the volatilomes on the antibiotic sensitivity of B. thuringiensis offering novel approaches to counter antibiotic resistance. Abstract : Stegodyphus dumicola nest microbiome members emit different blends of volatiles with diverse antimicrobial activities.